Economic Feasibility and Value Added Analysis of Bamboo Handicraft Industries in Rural Communities - Rahayu, Lestari; Wulandari, Atik Taqiyah; Rahmawati, Nur; Istiyanti, Eni (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2024)
AbstractBamboo is important in Indonesia's rural economy, especially in the craft sector. This study aimed to analyze the business feasibility and the added value of the bamboo craft industry. The study was conducted in Muntuk Village, Bantul Regency, Special Region of Yogyakarta Province, Indonesia through a quantitative descriptive approach with a census technique involving 100 bamboo artisans. Data were obtained through direct observation, structured interviews, and documentation of business activities. The feasibility analysis used the Revenue-to-Cost (R/C) ratio, while the added value was calculated using the Hayami method based on raw bamboo input-output. The results showed that all craft products (klakat, tampah, bamboo rice container, tambir) had an R/C ratio above 1 with the highest value was bamboo rice container of 5.48. The highest added value was the bamboo rice container, 325,903 rupiah per bamboo stick. Product diversification has increased the stability of artisan income, especially those who make more than one product type. Support for artisan skills, experience, and community-based management greatly determines product competitiveness. This study concludes that the bamboo craft industry in Muntuk Village is economically feasible to develop, and policy recommendations need to focus on skills training, digital marketing, and facilitation of artisan clusters.Keywords: bamboo, product diversification, business feasibility, crafts, added value Abstrak Bambu memiliki peran penting dalam ekonomi pedesaan Indonesia, khususnya dalam sektor kerajinan. Penelitian ini bertujuan menganalisis kelayakan usaha serta nilai tambah industri kerajinan bambu. Penelitian dilakukan di Desa Muntuk, Kabupaten Bantul, Provinsi Daerah Istimewa Yogyakarta, Indonesia melalui pendekatan deskriptif kuantitatif dengan teknik sensus melibatkan 100 perajin bambu. Data diperoleh melalui observasi langsung, wawancara terstruktur, dan dokumentasi kegiatan usaha. Analisis kelayakan menggunakan rasio R/C, sedangkan nilai tambah dihitung berdasarkan metode Hayami berbasis input-output bahan baku bambu. Hasil penelitian menunjukkan bahwa seluruh produk kerajinan (klakat, tampah, tempat nasi, tambir) memiliki rasio R/C di atas 1 dengan nilai tertinggi pada tempat nasi sebesar 5,48. Nilai tambah terbesar juga pada tempat nasi, yaitu 325.903 rupiah per batang bambu. Diversifikasi produk terbukti meningkatkan stabilitas pendapatan perajin, terutama yang membuat lebih dari satu jenis produk. Dukungan keterampilan perajin, pengalaman, serta pengelolaan berbasis komunitas sangat menentukan daya saing produk. Penelitian ini menyimpulkan industri kerajinan bambu Desa Muntuk layak dikembangkan secara ekonomi dan rekomendasi kebijakan perlu difokuskan pada pelatihan keterampilan, pemasaran digital, serta fasilitasi klaster perajin.Kata kunci: bambu, diversifikasi produk, kelayakan usaha, kerajinan, nilai tambah